Reliable Estimation of CD8 T Cell Inhibition of In Vitro HIV-1 Replication - Xu, Yinyan; Weideman, Ann Marie; Abad-Fernandez, Maria; Mollan, Katie R.; Kallon, Sallay; Samir, Shahryar; Warren, Joanna A.; Clutton, Genevieve; Roan, Nadia R.; Adimora, Adaora A.; Archin, Nancie; Kuruc, JoAnn; et al. (Frontiers in Immunology, 2021)
The HIV-1 viral inhibition assay (VIA) measures CD8 T cell-mediated inhibition of HIV replication in CD4 T cells and is increasingly used for clinical testing of HIV vaccines and immunotherapies. The VIA has multiple sources of variability arising from in vitro HIV infection and co-culture of two T cell populations. Here, we describe multiple modifications to a 7-day VIA protocol, the most impactful being the introduction of independent replicate cultures for both HIV infected-CD4 (HIV-CD4) and HIV-CD4:CD8 T cell cultures. Virus inhibition was quantified using a ratio of weighted averages of p24+ cells in replicate cultures and the corresponding 95% confidence interval. An Excel template is provided to facilitate calculations. Virus inhibition was higher in people living with HIV suppressed on antiretroviral therapy (n=14, mean: 40.0%, median: 43.8%, range: 8.2 to 73.3%; p<0.0001, Mann-Whitney test) compared to HIV-seronegative donors (n=21, mean: -13.7%, median: -14.4%, range: -49.9 to 20.9%) and was stable over time (n=6, mean %COV 9.4%, range 0.9-17.3%). Cross-sectional data were used to define 8% inhibition as the threshold to confidently detect specific CD8 T cell activity and determine the minimum number of culture replicates and p24+ cells needed to have 90% statistical power to detect this threshold. Last, we note that in HIV seronegative donors, the addition of CD8 T cells to HIV infected CD4 T cells, consistently increased HIV replication, though the level of increase varied markedly between donors. This co-culture effect may contribute to the poor correlations observed between CD8 T cell VIA and other measures of HIV-specific CD8 T cell function.